Calculation methods for cost management in the construction industry - Jazykbayeva, B.K.; Omarova, A.T.; Akhmetova, D.T.; Mussynova, A.M.; Nurseitova, G.B. (BUKETOV BUSINESS REVIEW, 2019)
Information on costs in the system of information on the activities of construction organizations plays a significant role in making managerial decisions, since the main indicators characterizing the activities of the organization are the volume of costs and the cost of production calculated on the basis of data on costs. The relevance of this article lies in the fact that the technology of construction production has a number of specific features that affect the organization of analytical and synthetic accounting of business entities. High competition, the search for reserves to reduce the cost of construction products and increase profitability require information on the real level of costs, rationality of use various resources. In the management system of a construction enterprise, an important place should be given to management of construction costs. The article also considers analytical tools and recommends a combined system for calculating the cost of construction products in the organization of management accounting, ensuring the adoption of effective management decisions of the construction company. When writing the article, general scientific methods of cognition (statistical, normative analysis, synthesis, analogy, generalization), empirical-theoretical (collecting, studying and comparing data), as well as methods of scientific cognition (historical and legal, systemic) were used. When processing and systematizing data, grouping and classification methods were used. The information-statistical base of the study was made up of data from official periodicals and informationanalytical publications of the Republic of Kazakhstan.